Strengthening Local Governance Through Effective Waste Management: The “Sustainable Environmental Practices and Policies” Program in South Lebanon and the Bekaa Valley - McCornack, Andrew (Consilience, 2012)
In response to the critical lack of solid waste and wastewater management facilities in towns and cities around Lebanon, the YMCA of Lebanon implemented the Sustainable Environmental Practices and Policies (SEPP) program from 2003 to 2009. The overall goal of the SEPP program was to improve environmental practices and policies for the management of both solid waste and wastewater in rural Lebanon. This included the Ain Baal solid waste treatment plant (SWTP) serving the city of Tyre and nine wastewater treatment plants in municipalities in southern and central areas of the nation. The project built the capacity of local governments, and it ensured the use of reliable, low cost, low maintenance technologies that improve long-term sustainability. The project attests to the hard work of national civil society organizations to improve environmental practices and increase the accountability of local governments. This project has helped reduce tensions between communities and foster more democratic participation at the local level.